Beneficial Effects of Sideritis scardica and Cichorium spinosum against Amyloidogenic Pathway and Tau Misprocessing in Alzheimer's Disease Neuronal Cell Culture Models - Chalatsa, I.; Arvanitis, DA; Mikropoulou, E. V.; Giagini, A.; Papadopoulou-Daifoti, Z.; Aligiannis, N; Halabalaki, M; Tsarbopoulos, A; Skaltsounis, L.A.; Sanoudou, D. (J Alzheimers DisJ Alzheimers DisJ Alzheimers Dis, 2018)
BACKGROUND: Natural products are a significantly underutilized source of potential treatments against human disease. Alzheimer's disease (AD) is a prime example of conditions that could be amenable to such treatments as suggested by recent findings. OBJECTIVE: Aiming to identify novel potentially therapeutic approaches against AD, we assessed the effects of Cichorium spinosum and Sideritis scardica extracts, both distinct components of the Mediterranean diet. METHODS/RESULTS: After the detailed characterization of the extracts' composition using LC-HRMS methods, they were evaluated on two AD neuronal cell culture models, namely the AbetaPP overexpressing SH-SY5Y-AbetaPP and the hyperphosphorylated tau expressing PC12-htau. Initially their effect on cell viability of SH-SY5Y and PC12 cells was examined, and subsequently their downstream effects on AbetaPP and tau processing pathways were investigated in the SH-SY5Y-AbetaPP and PC12-htau cells. We found that the S. scardica and C. spinosum extracts have similar effects on tau, as they both significantly decrease total tau, the activation of the GSK3beta, ERK1 and/or ERK2 kinases of tau, as well as tau hyperphosphorylation. Furthermore, both extracts appear to promote AbetaPP processing through the alpha, non-amyloidogenic pathway, albeit through partly different mechanisms. CONCLUSIONS: These findings suggest that C. spinosum and S. scardica could have a notable potential in the prevention and/or treatment of AD, and merit further investigations at the in vivo level.
Chalatsa, IoannaArvanitis, Demetrios AMikropoulou, Eleni VGiagini, AthinaPapadopoulou-Daifoti, ZetaAligiannis, NektariosHalabalaki, MariaTsarbopoulos, AnthonySkaltsounis, Leandros ASanoudou, DespinaengResearch Support, Non-U.S. Gov'tNetherlands2018/06/20 06:00J Alzheimers Dis. 2018;64(3):787-800. doi: 10.3233/JAD-170862.
Keywords: Amyloid beta-Peptides/metabolism; Amyloid beta-Protein Precursor/genetics/metabolism; Amyloidogenic Proteins/*metabolism; Animals; Asteraceae/chemistry; Cell Differentiation; Dose-Response Relationship, Drug; Humans; Neuroblastoma/pathology; Neurons/*drug effects; PC12 Cells; Plant Extracts/*pharmacology; Rats; Sideritis/chemistry; Signal Transduction/*drug effects; tau Proteins/genetics/*metabolism; Time Factors; Transfection